2023
DOI: 10.3390/plants12040850
|View full text |Cite
|
Sign up to set email alerts
|

Testing Explant Sources, Culture Media, and Light Conditions for the Improvement of Organogenesis in Pinus ponderosa (P. Lawson and C. Lawson)

Abstract: Pinus. ponderosa (P. Lawson and C. Lawson) is a commercial tree and one of the most important forest species in North America. Ponderosa pine suffers hardship when going through vegetative propagation and, in some cases, 15–30 years are needed to achieve full reproductive capacity. Based on previous works on P. ponderosa regeneration through in vitro organogenesis and trying to improve the published protocols, our objective was to analyze the influence of different types of explants, basal culture media, cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
2
0
1
Order By: Relevance
“…In Pinus pseudostrobus shoots exposed to red LEDs, the best rooting rates were observed at 30 days of evaluation [26]. Contrary to our results, P. radiata and P. ponderosa shoots grown under white fluorescent light and white LEDs, respectively, displayed the highest rooting responses [43,47]. Regarding LLR, shoots under fluorescent light showed longer primary roots.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In Pinus pseudostrobus shoots exposed to red LEDs, the best rooting rates were observed at 30 days of evaluation [26]. Contrary to our results, P. radiata and P. ponderosa shoots grown under white fluorescent light and white LEDs, respectively, displayed the highest rooting responses [43,47]. Regarding LLR, shoots under fluorescent light showed longer primary roots.…”
Section: Discussioncontrasting
confidence: 95%
“…However, in our study, no significant differences for the effect of CK on NS/E were found, but a slightly higher response in explants cultured with BA was observed (Experiment 2). Analogous results were obtained in P. radiata, S. sempervirens, and P. ponderosa, where the induction of axillary buds was not improved when applying m-T instead of BA [10,41,47,50].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation